Anti-ulcer activity of Centella asiatica leaf extract against ethanol-induced gastric mucosal injury in rats - Abdulla, M.A.; Al-Bayaty, F.H.; Younis, L.T.; Abu Hassan, M.I. (Academic Journals, 2010)
The present study was performed to evaluate the anti-ulcerogenic activity of ethanol extract of Centella asiatica against ethanol-induced gastric mucosal injury in rats. Five groups of adult Sprague Dawley rats were orally pre-treated respectively with carboxymethyl cellulose (CMC) solution (ulcer control group), Omeprazole 20 mg/kg (reference group), and 100, 200 and 400 mg/kg C. asiatica leaf extract in CMC solution (experimental groups), one hour before oral administration of absolute ethanol to generate gastric mucosal injury. Rats were sacrificed and the ulcer areas of the gastric walls were determined. Grossly, the ulcer control group exhibited severe mucosal injury, whereas pre-treatment with C. asiatica leaf extract exhibited significant protection of gastric mucosal injury. Histological studies revealed that ulcer control group exhibited severe damage of gastric mucosa, along with edema and leucocytes infiltration of submucosal layer compared to rats pre-treated with C. asiatica leaf extract which showed gastric mucosal protection, reduction or absence of edema and leucocytes infiltration of submucosal layer. Acute toxicity study did not manifest any toxicological signs in rats. The present finding suggests that C. asiatica leaf extract promotes ulcer protection as ascertained grossly and histologically compared to the ulcer control group.